Impact of economic liberalization on economic growth in the case of Pakistan / Qazi Muhammad Adnan Hye - Qazi Muhammad, Adnan Hye (2015)

(untitled)
Since late 1980s, Pakistan‟s policy makers have been following the economic liberalization policies, particularly financial and trade liberalization for attaining sustainable economic growth. Gauging the impact of such policies on Pakistan economic performance is indispensable to pave the way of sustainable economic growth. This study contributes to the existing literature in the case of Pakistan by estimating the impact of financial and trade liberalization on economic growth through the channels of private saving and investment. Further, this study also analyzes the determinants of capital account liberalization. Study applied autoregressive distributed lag approach (ARDL) on time series data from 1971 to 2013 for analyzing the objectives. The ARDL results indicate that the long run relationship exists in all models. First, the results of the economic growth model show that labor force (skill), capital stock, and financial liberalization index are positively related with the economic growth. The financial openness index and trade openness are negatively related to growth. Second, the long term results of the impact of financial and trade liberalization indicators on private saving show that per capita real private income, real deposit rate, public saving and financial liberalization index are positively linked with private saving. The capital account liberalization, financial openness index, and trade openness are negatively related to private saving in the long run. Third, the long term results of the impact of financial/trade liberalization indicators on private investment exhibit that per capita real private income, public investment, financial liberalization index are positively related to private investment in the long run. The real interest rate and trade openness are negatively linked to private investment in the long run. Last, the results of the impact of trade liberalization/openness on the capital account liberalization/openness highlight that trade openness (de facto) is positively related with capital account liberalization. Further, the results also indicate trade liberalization and iv trade openness are positively associated with the financial openness. Putting together, the overall results show that financial liberalization index is positively related to economic growth, private saving and investment. Against this backdrop, study suggests policy makers to promote financial liberalization in banking and stock sector as such liberalization policies are positively linked to economic growth. In the context of negative juxtaposition of capital account liberalization/openness to economic growth, there is need to relook at the capital account liberalization policies. The study also highlights a need to revise import liberalization policy of discouraging the imports of luxury consumer goods and subsidizing the machinery for industry. The control variable of skill labor force is positively linked to economic growth, thus this study suggests that skill labor is playing an important role in the growth process. Presently Pakistan is spending 2.1 % of GDP on education (GOP 2011), which is lower than other regional countries like India, Bangladesh and Nepal. An increase in education expenditures and their effective allocation is vital in order to sustain EG by improving the quality of human capital.